Pengaruh Literasi Keuangan Dan Pengendalian Diri Terhadap Perilaku Pengelolaan Keuangan Siswa Fase F Di SMKN 5 Padang - Reni Respita; Detman; Aisyah Ramadan Hikmah (Kilau Publishing, 2025)
This study aims to determine: (1) the influence of Financial Literacy on the Financial Management Behavior of Phase F students at SMKN 5 Padang; (2) the influence of Self- Control on the Financial Management Behavior of Phase F students at SMKN 5 Padang; and (3) the joint influence of Financial Literacy and Self-Control on the Financial Management Behavior of Phase F students at SMKN 5 Padang. The method used in this research is a quantitative approach. The population consisted of all Phase F students totaling 383 individuals, with a sample of 196 respondents selected using proportional random sampling. Data were collected through the distribution of questionnaires and tests. Hypothesis testing (F-test and t-test) and data analysis were conducted using multiple linear regression analysis with the help of the SPSS program.The results showed that: (1) financial literacy has a positive and significant influence on the financial management behavior of Phase F students, with a t-value of 3.707 > t-table 1.972 and a significance value of 0.000 < 0.05; (2) self- control has a positive and significant influence on the financial management behavior of Phase F students, with a t-value of 3.273 > t-table 1.972 and a significance value of 0.001 < 0.05; and (3) financial literacy and self-control together have a positive and significant influence on the financial management behavior of Phase F students, with an F-value of 25.123 > F-table 3.04 and a significance value of 0.000 < 0.05. Thus, the better the financial literacy and self-control, the better the students’ financial management behavior.